Negative electrode material, preparation method thereof and lithium ion battery

By forming a cladding layer with a reasonable pore structure on the core surface of the silicon-based negative electrode material, the problem of poor expansion and rate performance of silicon-based materials in lithium batteries is solved, and the electrochemical performance of the material and the improvement of battery efficiency is achieved.

CN119230808APending Publication Date: 2024-12-31BTR NEW MATERIAL GRP CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310809643.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have problems of large expansion and poor rate performance in lithium batteries, which affect their wide application.

Method used

By forming a cladding layer with a reasonable pore structure on the core surface of the silicon-based material, it isolates unnecessary exposure of silicon-based material, reduces the loss of active materials and lithium, improves cycling performance, and improves the transmission efficiency of lithium ions, and uses CVD vapor deposition to prevent unnecessary exposure of silicon-based material, reducing the loss of active materials and lithium-ion losses, improving the circulation performance, and improving the transmission efficiency of lithium ions. Handle the control hole structure.

Benefits of technology

It effectively alleviates material expansion, improves circulation and rate performance, and improves the Coulomb efficiency and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230808A_ABST
    Figure CN119230808A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material, a preparation method thereof and a lithium ion battery, and relates to the technical field of lithium ion batteries. The negative electrode material comprises a silicon-based material core and a coating layer formed on at least part of the surface of the silicon-based material core, wherein the coating layer has a pore structure; the differential pore structure ratio delta phi of the negative electrode material meets # imgabs0 #, wherein delta S is the area of a hysteresis loop in an isothermal adsorption and desorption curve of the negative electrode material; s is the specific surface area of the negative electrode material; delta P is the interval difference value of the relative pressure P / P0 corresponding to the hysteresis loop; qmax is the maximum isothermal adsorption capacity of the negative electrode material. The preparation method of the negative electrode material comprises the step of carrying out CVD (Chemical Vapor Deposition) treatment on a to-be-coated silicon-based material core to obtain the negative electrode material of which the coating layer has a pore structure. The coating layer with a special pore structure is arranged on the negative electrode material, so that the rate capability and the cycle performance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] At present, graphite materials are often used as negative electrode materials in mature commercial lithium-ion batteries. However, the theoretical lithium storage capacity of graphite materials is low and cannot meet people's demand for high energy density batteries. Silicon-based negative electrode materials have a very high theoretical capacity of about 4200mAh / g, which is much higher than the capacity of commercial graphite. Therefore, silicon-based negative electrode materials have great application prospects in energy storage and are one of the most critical materials for high energy density lithium-ion batteries.

[0003] However, existing silicon-based negative electrode materials have problems such as large expansion and poor rate performance, which seriously affect the widespread application of silicon-based negative electrode materials in lithium batteries. So, how to suppress expansion and improve the cycle rate performance of silicon-based materials is the premise for the widespread application of silicon-based negative electrode materials. Therefore, by designing the particle structure of silicon-based negative electrode materials, developing a negative electrode material that can alleviate expansion, improve rate performance and cycle performance is a difficult problem that needs to be overcome at this stage. Summary of the invention

[0004] The purpose of this application is to provide a negative electrode material and a preparation method thereof and a lithium-ion battery. By providing a coating layer with a reasonable pore structure, on the one hand, it can isolate unnecessary exposure of the silicon-based material core, reduce the loss of active materials and lithium, and improve the cycle performance; on the other hand, the pore structure is conducive to the rapid infiltration of the electrolyte, improves the transmission efficiency of lithium ions, and thus improves the rate performance of the material.

[0005] To achieve the above objectives, the technical solution of this application is as follows:

[0006] In a first aspect, the present application provides a negative electrode material, comprising a silicon-based material core and a coating layer formed on at least a portion of the surface of the silicon-based material core, wherein the coating layer has a pore structure;

[0007] The differential ratio of the pore structure Satisfaction: 1×10 -3 ≤ΔΦ≤0.5;

[0008] Wherein, ΔS is the area of ​​the hysteresis loop in the isothermal adsorption-desorption curve of the negative electrode material;

[0009] s is the specific surface area of ​​the negative electrode material;

[0010] ΔP is the interval difference of the relative pressure P / P0 corresponding to the hysteresis loop, 0<ΔP≤1;

[0011] Qmax is the maximum isothermal adsorption capacity of the negative electrode material.

[0012] In combination with the first aspect, in a preferred embodiment, the negative electrode material satisfies at least one of the following conditions a1:

[0013] a. The silicon-based material core includes at least one of elemental silicon, silicon oxide, silicon carbide, silicon nitride, silicon phosphide, silicon sulfide, and silicon alloy;

[0014] b. The coating layer comprises at least one of a carbonaceous material and a ceramic material;

[0015] c. The mass of the coating layer is 0.5%-10% of the total mass of the negative electrode material;

[0016] d. The thickness of the coating layer is 20nm-700nm;

[0017] e. The silicon-based material core also includes a carbon-based substance;

[0018] f. The silicon-based material core further includes a doped metal;

[0019] g. The differential ratio ΔΦ of the pore structure satisfies 5×10 -3 ≤ΔΦ≤0.5;

[0020] h. The area of ​​the hysteresis loop ΔS satisfies 4.5×10 -4 ≤ΔS≤2.5×10 -2 ;

[0021] i. The specific surface area s of the negative electrode material is 0.5m 2 / g-15m 2 / g;

[0022] j. The maximum isothermal adsorption capacity Q of the negative electrode material max ≤1.35mmol / g;

[0023] k. The BJH average pore size of the negative electrode material is 5nm-20nm, and the BJH pore volume satisfies 1.0×10 -4 cm 3 / g≤V BJH ≤0.1cm 3 / g;

[0024] 1. The pH of the negative electrode material is 6.0-12.0.

[0025] Further preferably, the negative electrode material also satisfies at least one of the following conditions mq:

[0026] m. The carbonaceous material comprises at least one of graphite, hard carbon, soft carbon, amorphous carbon, diamond-like carbon, carbon fiber, carbide, asphalt, and resin-based polymers;

[0027] n. The ceramic material includes at least one of phosphates, silicates, nitrides and metal oxides;

[0028] o. The carbon material includes at least one of soft carbon, hard carbon, amorphous carbon, graphite, graphene, carbon nanotubes, carbon fiber, and diamond-like carbon;

[0029] p. The doping metal includes at least one of Li, Mg, Al, Ti, Na, K, Ca, Be, La, Ce, V, and Ba;

[0030] q. The mass percentage of the doped metal in the negative electrode material is 2%-15%.

[0031] In combination with the first aspect, in a preferred embodiment, the pore structure of the coating layer includes micropores, mesopores and macropores.

[0032] In a second aspect, the present application provides a method for preparing a silicon-based negative electrode material, comprising:

[0033] Performing CVD vapor deposition treatment on the silicon-based material core to be coated to obtain a negative electrode material with a pore structure in the coating layer;

[0034] The gas for vapor deposition includes a mixed gas including an auxiliary gas and a carbon source gas.

[0035] In conjunction with the second aspect, in a preferred embodiment, the preparation method satisfies at least one of the following conditions:

[0036] A. Before the CVD vapor deposition process, the silicon-based material core to be coated is pretreated;

[0037] B. The temperature of the vapor deposition treatment is 400°C-1200°C, and the time is 1h-12h;

[0038] C. When the CVD vapor deposition process is performed, it also includes: placing the silicon-based material core to be coated in a deposition chamber of a deposition furnace, the rotation speed of the deposition chamber is 0.1r / min-10r / min, and the gas pressure in the deposition furnace is 0.1MPa-10MPa;

[0039] D. The carbon source gas includes at least one of methane, ethane, ethylene, acetylene, propane, formaldehyde, acetaldehyde, and methanol;

[0040] E. The auxiliary gas includes at least one of H2, SO2, NH3, and Ar;

[0041] F. In the mixed gas, the volume proportion of the carbon source gas is 30%-95%, and the volume proportion of the auxiliary gas is 5%-70%.

[0042] Further preferably, the preparation method further satisfies at least one of the following conditions:

[0043] G. The pretreatment includes: screening, grading, cleaning and drying in sequence;

[0044] H. The particle size D of the silicon-based material core to be coated obtained after the pretreatment 50 =2.5μm-9.0μm;

[0045] I. The specific surface area of ​​the silicon-based material core to be coated obtained after the pretreatment is 0.5 m 2 / g-7.5m 2 / g.

[0046] Furthermore, the preparation method satisfies at least one of the following conditions:

[0047] J. The cleaning comprises: first washing with water and then rinsing with an organic solvent;

[0048] K. The drying comprises: air-drying the cleaned material using an inert gas, and then vacuum drying the cleaned material in an environment of 60° C.-150° C. and below 1000 Pa.

[0049] In combination with the second aspect, in a preferred embodiment, after the vapor deposition process, the method further includes: grading and drying the product obtained by the vapor deposition process.

[0050] In a third aspect, the present application further provides a lithium-ion battery, comprising the negative electrode material described in the first aspect, or comprising the negative electrode material prepared by the preparation method described in the second aspect.

[0051] Beneficial effects of this application:

[0052] The present application provides a negative electrode material with a coating layer, wherein the coating layer has a pore structure, and through research, it is found that the pore structure has a great influence on the electrochemical performance of the negative electrode material, so the pore structure of the negative electrode material is studied in detail, and by studying the law of adsorption defects, it is found that the data curve characteristics of the hysteresis loop of the isothermal adsorption and desorption curve of the negative electrode material are highly correlated with the electrochemical performance, and there is a preferred mathematical relationship range (pore structure differentiation ratio ΔΦ), which can maximize the electrochemical performance of the negative electrode material within the range. When ΔΦ is too small, the pore differentiation is small, the pore structure is simple, the interface reaction is strong, the SEI stability is poor, the expansion is large, and the cycle is poor. When ΔΦ is too large, the pore structure is complex, and the extremely fine micropores are interlaced with the main pores, resulting in poor electrolyte wettability, large mass transfer resistance, and rate difference. Therefore, when ΔΦ is in a suitable numerical range, the pore structure can optimize the interface reaction, improve the interface space utilization, alleviate material expansion, balance the mass transfer efficiency, balance the interaction between SEI growth and core expansion, and improve the electrochemical performance of the material.

[0053] In the negative electrode material preparation method provided in the present application, a negative electrode material having a pore structure in the coating layer is prepared by using CVD vapor deposition treatment. Among them, by introducing auxiliary gas into the carbon source gas, the pore structure in the coating layer and the pore structure between the coating layer and the core can be regulated, and the complexity of the pore structure in the coating layer can be further improved. By changing the pore structure, the differentiation ratio of the pore structure is changed, and the electrochemical performance of the negative electrode material is changed.

[0054] The above-mentioned negative electrode material is used in the lithium-ion battery provided in the present application. By utilizing the reasonable pore structure in the coating layer, the negative electrode material can quickly transfer mass and charge, and the pores in the coating layer can also buffer the expansion of the negative electrode material, stabilize the SEI interface, and greatly reduce the deposition thickness of the SEI layer, thereby greatly improving the diffusion coefficient of the lithium core of the negative electrode material and improving the coulombic efficiency and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0056] Figure 1 Isothermal adsorption-desorption curve of the negative electrode material prepared in Example 1;

[0057] Figure 2 This is the isothermal adsorption-desorption curve of the negative electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0058] As used herein:

[0059] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus. The conjunction "consisting of" excludes any unspecified element, step, or component.

[0060] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0061] In these examples, parts and percentages are by mass unless otherwise indicated.

[0062] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0063] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0064] Although silicon-based negative electrode materials have high energy density, they have excessive volume expansion during the charge and discharge process, resulting in problems such as poor cycle and rate performance. In response to this, the inventors of this application designed the particle structure of the negative electrode material to improve the performance of the material. After research, it was found that the size of the pores in the surface coating layer of the negative electrode material plays a key role.

[0065] First, the appropriate pore distribution and pore structure are conducive to the rapid infiltration of the electrolyte. This rapid infiltration improves the rapid transmission of lithium ions, shortens the lithium ion transmission path, and improves the lithium ion transmission efficiency, thereby improving the material rate performance. In addition, the coating layer on the surface of the negative electrode material can effectively isolate the co-embedding of organic small molecules in the electrolyte, reduce the loss of the core material, and improve the cycle performance.

[0066] However, in most studies, only some specifications are made for the specific surface area and pore size range of the material, and the relationship between pore size, pore shape, pore structure, etc. and electrochemical performance is not studied in depth, and further improvements cannot be made. The pores on the surface of the negative electrode material serve as fast transmission channels for lithium transmission, core expansion space, and skeleton space for SEI deposition, which is conducive to alleviating core expansion, improving cycle and rate performance, stabilizing the SEI-active component interface, improving cycle coulomb efficiency, and reducing the loss of active silicon and lithium. Based on this, the inventors of this application have conducted in-depth research on the pore structure of the negative electrode material.

[0067] In a first aspect, the present application provides a negative electrode material, comprising a silicon-based material core and a coating layer formed on at least a portion of the surface of the silicon-based material core, wherein the coating layer has a pore structure.

[0068] Among them, the differentiation ratio of pore structure Satisfaction: 1×10 -3 ≤ΔΦ≤0.5, for example, ΔΦ can be 0.001, 0.003, 0.005, 0.008, 0.01, 0.05, 0.1, 0.5 or any value between 0.001 and 0.5. More preferably, 5×10 -3 ≤ΔΦ≤0.5.

[0069] Specifically, ΔS is the area of ​​the hysteresis loop in the isothermal adsorption-desorption curve of the negative electrode material, which is the area of ​​the hysteresis loop calculated using the integration method; s is the specific surface area of ​​the negative electrode material, and the value of the specific surface area is selected in units of m 2 / g corresponds to the specific value; ΔP is the interval difference of the relative pressure P / P0 corresponding to the hysteresis loop, 0<ΔP≤1, for example, if the relative pressure P / P0 corresponding to the hysteresis loop in the isothermal adsorption-desorption curve is in the range of 0.6-0.9, then ΔP=0.9-0.6=0.3, or if the relative pressure P / P0 corresponding to the hysteresis loop is in the range of 0.53-0.76, then ΔP=0.76-0.53=0.23; Q max It is the maximum isothermal adsorption capacity of the negative electrode material. This value is the specific value corresponding to the unit of mmol / g.

[0070] It should be noted that the present application tests the pore structure in the negative electrode material by gas adsorption method, and the detection instrument used is an pore size analyzer. By placing an accurately weighed sample to be tested in a sample tube, the whole system reaches the required vacuum degree by vacuum degassing, and then the sample tube is immersed in a liquid nitrogen bath and filled with a known amount of gas (nitrogen). The sample adsorption gas will cause a pressure drop. After reaching adsorption equilibrium, the equilibrium pressure of the gas is measured, and the adsorption amount can be calculated according to the pressure change of the system before and after adsorption. The amount of adsorbate gas is gradually increased to the system to change the pressure, and the above operation is repeated to test the isothermal adsorption and desorption curve, and then the theoretical model is used to equivalently calculate the specific surface area, pore volume and pore size distribution of the sample to be tested. As for the area size of the hysteresis loop, it is mainly obtained by integrating the adsorption curve and the desorption curve in the isothermal adsorption and desorption curve respectively, and then subtracting the data.

[0071] The inventor of this application discovered that the data curve characteristics of the hysteresis loop of the isothermal adsorption-desorption curve of the negative electrode material have a great correlation with the electrochemical performance through the law of adsorption defects. The pore structure in the silicon-based negative electrode material is described by using the hysteresis loop area and the corresponding relative pressure interval difference, material specific surface area and maximum isothermal adsorption amount and other data, and combined into a calculation formula to obtain the differentiated pore structure ratio ΔΦ, which shows the influence of the pore structure of the material on the electrochemical performance of the material, and converts the contribution of the pore structure into an equivalent ratio to determine the efficiency of interfacial mass transfer and charge transfer.

[0072] When ΔΦ is too small, the pore differentiation is small, the pore structure is simple, and there are few combinations of different pore structures. Therefore, under the same specific surface area conditions, the material with this pore structure has high pore utilization, low expansion mitigation efficiency, poor SEI interface stability, and low cycle performance, especially low cycle Coulomb efficiency. When ΔΦ is too large, the pore structure is complex, and channels of different pore sizes are combined with each other, resulting in strong mass transfer resistance, low mass transfer efficiency, poor rate, and aggravated concentration polarization. Therefore, a reasonable pore structure distribution and a suitable staggered structure require that while ensuring rapid mass-charge transfer of the material, there must also be sufficient pores to buffer the expansion of the inner core, stabilize the SEI interface, and improve the Coulomb efficiency.

[0073] In combination with the first aspect, in a preferred embodiment, the silicon-based material core in the negative electrode material of the present application includes at least one of elemental silicon, silicon oxide, silicon carbide, silicon nitride, silicon phosphide, silicon sulfide, and silicon alloy. Among them, the silicon oxide can be a silicon-oxygen composite, in which the molar ratio of oxygen atoms to silicon atoms is (0.5-2):1.

[0074] In addition to silicon-based materials, the silicon-based material core may also include at least one of carbon-based materials and doped metals. More preferably, the silicon-based material core is mainly in the form of elemental silicon, silicon alloys, silicates, etc. together with other silicon-based materials to form the core. When a metal-doped core exists in the silicon-based material core, the doped metal exists in the form of silicates.

[0075] For doped silicon-based negative electrode materials, such as a core composed of doped metal combined with elemental silicon, or a core composed of silicate combined with silicon oxide, such a multi-element core makes the deposition rate of the coating layer on the surface of the core further different (the deposition efficiency of elemental silicon, silicon oxide, and silicate surfaces is different), thereby making the differentiated performance of the coating layer structure and pore structure more prominent, and the differentiated value is closer to the center value of the preferred range, effectively improving the electrochemical rate performance and the cycle capacity retention rate.

[0076] Further preferably, the carbon-based material includes at least one of soft carbon, hard carbon, amorphous carbon, graphite, graphene, carbon nanotubes, carbon fiber, and diamond-like carbon.

[0077] Further preferably, the doping metal includes at least one of Li, Mg, Al, Ti, Na, K, Ca, Be, La, Ce, V, and Ba.

[0078] Further preferably, the doping mass percentage of the doped metal in the negative electrode material is 2%-15%, for example, it can be 2%, 3%, 5%, 8%, 10%, 12%, 15% or any value between 2% and 15%.

[0079] In a preferred embodiment, the coating layer in the negative electrode material of the present application includes at least one of a carbonaceous material and a ceramic material.

[0080] Further preferably, the carbon-containing material includes at least one of graphite, hard carbon, soft carbon, amorphous carbon, diamond-like carbon, carbon fiber, carbide, asphalt, and resin-based high molecular polymers.

[0081] Further preferably, the ceramic material includes at least one of phosphate, silicate, nitride and metal oxide.

[0082] In a preferred embodiment, the mass of the coating layer is 0.5%-10% of the total mass of the negative electrode material, for example, it can be 0.5%, 1%, 3%, 5%, 7%, 10% or any value between 0.5% and 10%, more preferably 2.5%-8%.

[0083] In a preferred embodiment, the thickness of the coating layer is 20 nm-700 nm, for example, it can be 20 nm, 50 nm, 100 nm, 200 nm, 300 nm, 500 nm, 700 nm or any value between 20 nm and 700 nm.

[0084] In a preferred embodiment, the differential pore structure ratio ΔΦ of the negative electrode material satisfies 5×10 -3 ≤ΔΦ≤0.5.

[0085] In a preferred embodiment, there is a hysteresis loop in the isothermal adsorption-desorption curve of the negative electrode material, and the area ΔS of the hysteresis loop satisfies 4.5×10 -4 ≤ΔS≤2.5×10 -2 , for example, ΔS can be 0.00045, 0.0005, 0.001, 0.005, 0.01, 0.02, 0.025 or any value between 0.00045 and 0.025. Further preferably, 4.5×10 -4 ≤ΔS≤1.0×10 -2 .

[0086] In a preferred embodiment, the specific surface area s of the negative electrode material is 0.5 m 2 / g-15m 2 / g, for example, it can be 0.5m 2 / g, 1m 2 / g, 3m 2 / g, 5m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 15m 2 / g or 0.5m 2 / g-15m 2 / any value between, more preferably 0.5m 2 / g-10m 2 / g.

[0087] In a preferred embodiment, the maximum isothermal adsorption capacity Q of the negative electrode material is max ≤1.35mmol / g, for example, it can be 0.1mmol / g, 0.3mmol / g, 0.5mmol / g, 0.8mmol / g, 1.0mmol / g, 1.2mmol / g or 1.35mmol / g.

[0088] In a preferred embodiment, the BJH average pore size of the negative electrode material is 5 nm-20 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm or any value between 5 nm and 20 nm.

[0089] The BJH pore volume of the negative electrode material, also known as the BJH Adsorption cumulative volume of pores, satisfies 1.0×10 -4 cm 3 / g≤V BJH ≤0.1cm 3 / g, for example V BJH Can be 0.0001cm 3 / g, 0.0005cm 3 / g, 0.001cm 3 / g, 0.005cm 3 / g, 0.01cm 3 / g, 0.05cm 3 / g, 0.1cm 3 / g or 1.0×10 - 4 cm 3 / g-0.1cm 3 Any value between / g.

[0090] In a preferred embodiment, the pH of the finished negative electrode material is 6.0-12.0, for example, it can be 6.0, 6.5, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0 or any value between 6.0 and 12.0.

[0091] In a preferred embodiment, the coating layer of the negative electrode material has a microporous structure, a mesoporous structure and a macroporous structure. Specifically, the pore structure of the coating layer is mainly mesoporous, the pore volume of the mesopores is preferably in the range of 65-90%, the macropores are preferably in the range of 5%-20%, and the micropores are preferably in the range of 0.05-10%.

[0092] In the second aspect, the present application provides a method for preparing a negative electrode material, comprising: performing CVD vapor deposition treatment on the core of a silicon-based material to be coated to obtain a negative electrode material with a porous structure in the coating layer; wherein the gas for the vapor deposition treatment includes a mixed gas including an auxiliary gas and a carbon source gas.

[0093] In combination with the second aspect, in a preferred embodiment, before the CVD vapor deposition process is performed, the silicon-based material core to be coated is also pre-treated.

[0094] Further preferably, the pretreatment includes: screening, grading, washing and drying in sequence.

[0095] The cleaning includes: first washing with water, and then rinsing with an organic solvent; the drying includes: air-drying the cleaned material with an inert gas, and then vacuum drying in an environment of 60°C-150°C and below 1000Pa;

[0096] Specifically, the core of the silicon-based material to be coated is vibrated and sieved, and the appropriate particle size (D 50 The preferred range is 2.5μm-9.0μm); then rinse with deionized water for 30min, then rinse with ethanol for 30min, and finally purge and dry with argon. The purge-dried material is further vacuum dried, requiring the vacuum environment to be maintained below 1000Pa, the drying temperature to be in the range of 60℃-150℃, and the drying time can be any value between 3h-48h.

[0097] It should be noted that, by pre-treating the particle size of the silicon-based material core to be coated, the specific surface area of ​​the silicon-based material core raw material is effectively controlled (preferably the specific surface area is in the range of 0.5 m 2 / g-7.5m 2 / g), which has a certain control effect on the formation of pore structure after deposition.

[0098] In addition, washing methods such as water washing and alcohol washing can clean the adsorbents on the surface of the core, reduce the influence of the adsorbents on the deposition, and enable the coating layer to form a chemical bond with the core tightly, which is conducive to the rapid transfer of charge and improves the conductivity of the material. Moreover, the surface adsorbents have a certain influence on the deposition structure of the coating layer, increase the uncertainty of the formation of the negative electrode material, and affect the material performance.

[0099] In a preferred embodiment, the temperature of the CVD vapor deposition treatment is 400℃-1200℃, for example, it can be 400℃, 600℃, 800℃, 1000℃, 1200℃ or any value between 400℃-1200℃; the time is 1h-12h, for example, it can be 1h, 3h, 5h, 7h, 10h, 12h or any value between 1h-12h.

[0100] In a preferred embodiment, the CVD vapor deposition process further includes: placing the silicon-based material core to be coated in a deposition chamber of a deposition furnace, wherein the rotation speed of the deposition chamber is 0.1 r / min-10 r / min, and the gas pressure in the deposition furnace is 0.1 MPa-10 MPa.

[0101] It should be noted that the temperature of CVD vapor deposition can regulate the deposition efficiency, the gas pressure in the furnace can control the density of the coating layer, the deposition time can control the thickness of the coating layer, and the rotation of the deposition chamber can improve the uniformity of the deposition coating between particles.

[0102] In a preferred embodiment, the carbon source gas used in the CVD vapor deposition process includes at least one of methane, ethane, ethylene, acetylene, propane, formaldehyde, acetaldehyde, and methanol.

[0103] More preferably, at least two different carbon source gases are used in the CVD vapor deposition process, because the dissociation temperatures and dissociation efficiencies of the different carbon source gases are different, which will form differential deposition, and the coating layer with a complex pore structure combination can be deposited by using the differential deposition of different gas sources.

[0104] In a preferred embodiment, the auxiliary gas used in the CVD vapor deposition process includes at least one of H2, CO2, NH3, and Ar.

[0105] Preferably, in the mixed gas, the volume proportion of the carbon source gas is 30%-95%, and the volume proportion of the auxiliary gas is 5%-70%. For example, the carbon source gas accounts for 30% and the auxiliary gas accounts for 70%; or the carbon source gas accounts for 50% and the auxiliary gas accounts for 50%; or the carbon source gas accounts for 80% and the auxiliary gas accounts for 20%; or the carbon source gas accounts for 95% and the auxiliary gas accounts for 5%.

[0106] It should be noted that by introducing different proportions of carbon source gas and auxiliary gas, the number of carbon layer terminals can be controlled, thereby increasing the proportion of deposited carbon chain terminals formed during the deposition process, further improving the complexity of the pore structure in the material, and changing the pore structure, thereby changing the differentiated pore structure ratio and changing the electrochemical performance.

[0107] In a preferred embodiment, after CVD vapor deposition, the obtained product needs to be graded and dried, and then packaged to form a finished negative electrode material.

[0108] In a preferred embodiment, the negative electrode material of the present application can also be obtained by liquid-phase coating or solid-phase coating of the silicon-based material core to be coated.

[0109] Further preferably, the liquid phase coating comprises: dissolving the coating raw material in a solvent, and then mixing it with the silicon-based material core to be coated to obtain a precursor solution; evaporating the precursor solution, and then placing it in an inert gas for a first heat treatment to obtain the negative electrode material.

[0110] If the coating layer is a ceramic material, the coating raw material used in the liquid phase coating includes at least one of soluble silicates, phosphates, and metal salts, and the solvent used is water.

[0111] If the coating layer is a carbonaceous material, the coating raw material used in the liquid phase coating includes at least one of asphalt and resin-based high molecular organic compounds, and the solvent used includes at least one of n-hexane, benzene and toluene.

[0112] It should be noted that the use of a variety of asphalt, polymer monomers and other materials dissolved in organic solvents, their complex cross-linking polymerization, and differentiated deposition are conducive to the synthesis of complex pore structures. For polar solvents, adding soluble mixed organic monomers can form polymers under certain pH conditions and then perform precursor synthesis deposition.

[0113] In a preferred embodiment of liquid phase coating, the mass of the coating raw material is 0.5%-10% of the total mass of the coating raw material and the silicon-based material core to be coated, for example, it can be 0.5%, 1%, 3%, 5%, 8%, 10% or any value between 0.5%-10%. This is mainly to ensure that the coating raw material can be uniformly deposited on the surface of the core.

[0114] The ratio of the mass of the solvent to the mass of the silicon-based material core to be coated is (3-7.5):1, for example, it can be 3:1, 4:1, 5:1, 6:1, 7:1, 7.5:1 or any value between (3-7.5):1.

[0115] When the precursor solution is evaporated, it includes: placing the precursor solution in a water bath or an oil bath for heating and evaporation, and stirring the precursor solution at a speed of 10r / min-500r / min. The temperature of the water bath or the temperature of the oil bath is within the range of 10℃-20℃ lower than the boiling point of the solvent. For example, when the solvent is water, the water bath temperature is set in the range of 80℃-90℃; stirring until the particles are completely dry and reappear in powder form.

[0116] After the evaporated material is placed in an inert gas for the first heat treatment, the precursor can undergo a solid phase reaction to form a silicate, and some carbon-containing materials can be carbonized to form a coating layer, thereby improving the conductivity of the negative electrode material. Specifically, the precursor can form a ceramic coating layer through a solid phase reaction, because the precursor material can be uniformly deposited on the surface of the active core through coprecipitation and sol-gel methods, and various components are uniformly mixed, which can reduce the reaction temperature and improve the reaction efficiency and the ceramic body forming efficiency.

[0117] In a preferred embodiment of liquid phase coating, the temperature of the first heat treatment is 500°C-1200°C, for example, 500°C, 600°C, 800°C, 1000°C, 1200°C or any value between 500°C-1200°C. The time of the first heat treatment is 3h-24h, for example, 3h, 5h, 10h, 15h, 20h, 24h or any value between 3h-24h. The inert gas used includes at least one of argon, nitrogen and helium.

[0118] In a preferred embodiment, when using a solid phase coating process, it specifically includes: solid-phase mixing the solid coating material with the silicon-based material core to be coated to obtain a solid-phase precursor; placing the solid-phase precursor in an inert gas for a second heat treatment to obtain a negative electrode material.

[0119] Among them, the solid coating material includes at least one of solid asphalt, soft carbon, hard carbon, and ceramic precursor materials. Due to the difference in carbon structure between these coating materials, after being evenly mixed by ball milling, each phase can be fully combined and evenly deposited on the surface of the silicon-based material core, which can reduce the reaction temperature and is conducive to the combination of internal pore structures of each structure during the later sintering process to form a better internal structure. Further preferably, the ball milling time is 6h-72h.

[0120] In a preferred embodiment of solid phase coating, the temperature of the second heat treatment is 500°C-1200°C, for example, it can be 500°C, 600°C, 800°C, 1000°C, 1200°C or any value between 500°C and 1200°C; the time is 3h-24h, for example, it can be 3h, 5h, 10h, 15h, 20h, 24h or any value between 3h-24h.

[0121] After the liquid phase coating or solid phase coating is completed, the method further includes: etching and washing the obtained product. Specifically, after acid-base etching, washing and filtration, argon gas is used for drying, and then the argon-dried product can be graded and vacuum dried, and after removing moisture, vacuum packaged to form a finished negative electrode material.

[0122] It should be noted that by subjecting the product obtained after liquid phase coating or solid phase coating to acid-base etching, water washing, and grading treatment, the unreacted soluble precursor in the product can be removed, and the pore structure in the product can be further improved. Among them, grading the washed and dried product can break up the agglomeration of the powder, and further control the graded negative electrode material to be within the optimized particle size range. In addition, because the negative electrode material containing a porous structure is easy to absorb moisture, the moisture is further removed by vacuum drying, thereby improving the electrochemical performance of the negative electrode material.

[0123] The present application controls the pores of the negative electrode material by regulating the coating layer, especially the coating layer with a special characteristic pore structure, which can effectively alleviate the expansion of the negative electrode core, balance the stability of the SEI growth interface, improve the cycle coulomb efficiency, and ensure the performance of the negative electrode material.

[0124] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0125] Example 1

[0126] This embodiment provides a negative electrode material, and the preparation method thereof includes:

[0127] (1) Weigh 1000 g of lithium-doped silicon oxide, in which the mass proportion of lithium is 10% and the silicon / oxygen atomic ratio is between 1:0.9 and 1.1, rinse with deionized water for 30 minutes, then rinse with ethanol for 30 minutes, and then blow with dry Ar until there is no obvious liquid and there is no adhesion or agglomeration between the particles. Then put it in a vacuum drying oven. When the pressure in the oven drops to 500 Pa, start heating and drying. The drying temperature is 100°C and the drying time is 24 hours.

[0128] (2) Place the treated sample in a vapor deposition furnace for coating. The coating gas is a mixture of methane, acetylene, and ethylene, with a volume ratio of 1:1:1, and NH3 auxiliary atmosphere is introduced, and the volume ratio of carbon source gas to auxiliary gas is 1:1. The deposition temperature is 900°C, the deposition time is 5h, and the deposition chamber speed is 5r / min; the air pressure in the deposition chamber is regulated by the air pressure valve, and the air pressure is maintained at 0.5MPa, and the mass proportion of the coating layer is controlled to be (5±0.5)%.

[0129] (3) The samples after vapor deposition are graded, the materials are screened and adjusted to a target particle size, and vacuum dried at 100° C. for 24 hours to form a finished negative electrode material.

[0130] Example 2

[0131] This embodiment provides a negative electrode material, and the preparation method thereof includes:

[0132] (1) Weigh 1000 g of lithium-doped silicon oxide, in which the mass proportion of lithium is 10% and the silicon / oxygen atomic ratio is between 1:0.9 and 1.1, rinse with deionized water for 30 minutes, then rinse with ethanol for 30 minutes, and then blow with dry Ar until there is no obvious liquid and there is no adhesion or agglomeration between the particles. Then put it in a vacuum drying oven. When the pressure in the oven drops to 500 Pa, start heating and drying. The drying temperature is 100°C and the drying time is 24 hours.

[0133] (2) Place the processed sample in a vapor deposition furnace for coating. The coating gas is a mixture of methane and acetylene with a volume ratio of 1:1, and an Ar auxiliary atmosphere is introduced. The ratio of carbon source gas to auxiliary gas is 1:1. The deposition temperature is 900°C, the deposition time is 5h, and the deposition chamber speed is 5r / min; the air pressure in the deposition chamber is regulated by the air pressure valve, and the air pressure is maintained at 0.3MPa. The mass ratio of the coating layer is controlled to be (5±0.5)%.

[0134] (3) The samples after vapor deposition are graded, the materials are screened and adjusted to a target particle size, and vacuum dried at 100° C. for 24 hours to form a finished negative electrode material.

[0135] Example 3

[0136] This embodiment provides a negative electrode material, and its preparation method is the same as that of Embodiment 1, except that: in step (1), 1000 g of silicon 2 oxide is weighed, wherein the silicon / oxygen atomic ratio is between 1:0.9 and 1.1.

[0137] Example 4

[0138] This embodiment provides a negative electrode material, and the preparation method thereof is the same as that of Embodiment 1, except that the ratio of the carbon source gas to the auxiliary gas is 1:3.

[0139] Example 5

[0140] This embodiment provides a negative electrode material, and the preparation method thereof is the same as that of Embodiment 1, except that the ratio of the carbon source gas to the auxiliary gas is 1:4.

[0141] Example 6

[0142] The present embodiment provides a negative electrode material, and its preparation method is the same as that of embodiment 1, except that: in step (1), 1000g of magnesium aluminum doped silicon dioxide is weighed, the mass proportion of magnesium is 5%, the mass proportion of aluminum is 5%, and the silicon / oxygen atomic ratio is between 1:0.9 and 1.1.

[0143] Example 7

[0144] This embodiment provides a negative electrode material, and the preparation method thereof includes:

[0145] (1) Weigh 1000g of silicon 2 oxide, where the silicon / oxygen atomic ratio is between 1:0.9 and 1.1. Rinse with deionized water for 30 minutes, then rinse with ethanol for 30 minutes, and then purge with dry Ar until there is no obvious liquid and there is no adhesion or agglomeration between particles. Then put it in a vacuum drying oven, and the pressure in the oven drops to 500Pa. Start heating and drying, the drying temperature is 100℃, and the drying time is 24h.

[0146] (2) Place the treated sample in a vapor deposition furnace for coating. Methane gas is selected as the coating gas, and H2 and SO2 are introduced into the auxiliary atmosphere. The volume ratio of the two auxiliary gases is 1:1, and the ratio of the carbon source gas to the auxiliary gas is 1:2. The deposition temperature is 900°C, the deposition time is 7h, and the deposition chamber speed is 5r / min; the air pressure in the deposition chamber is regulated by the air pressure valve, and the air pressure is maintained at 1MPa. The mass ratio of the coating layer is controlled to be (5±0.5)%.

[0147] (3) The samples after vapor deposition are graded, the materials are screened and adjusted to a target particle size, and vacuum dried at 100° C. for 24 hours to form a finished negative electrode material.

[0148] Comparative Example 1

[0149] This comparative example provides a negative electrode material, and the preparation method thereof comprises:

[0150] (1) 100 g of silicon 2 oxide, wherein the silicon / oxygen atomic ratio is between 1:0.9 and -1.1, is added to an organic solvent in which 100 g of N-methylpyrrolidone and 20 g of polyimide are mixed and dissolved, stirred for 30 min, and then vacuum dried at a drying temperature of 100° C. for 48 h to remove the solvent.

[0151] (2) The mixed precursors were transferred into a high-pressure reactor, and the temperature was raised to 900° C. at a rate of 10° C. / min under an argon atmosphere, and the reaction was continued for 12 h.

[0152] (3) The samples after vapor deposition are graded, and the materials are screened and adjusted to the target particle size; the heat-treated materials are then placed in a hydrochloric acid solution with a pH of 2 for 30 minutes, rinsed with deionized water, and then placed in a lithium hydroxide solution with a pH of 11 for 30 minutes, washed with deionized water for 30 minutes, and further rinsed with ethanol and filtered for 30 minutes, and purged with dry argon gas. After the samples are obviously free of adherent liquid and agglomerated particles, they are placed in a vacuum drying oven and vacuum dried at 100°C for 24 hours to form a finished negative electrode material.

[0153] Comparative Example 2

[0154] This comparative example provides a negative electrode material, and the preparation method thereof comprises:

[0155] (1) Weigh 100 g of lithium-doped silicon oxide, in which the lithium content is 10% by weight and the silicon / oxygen atomic ratio is between 1:0.9 and 1.1, rinse with deionized water for 30 min, then rinse with ethanol for 30 min, and then blow with dry Ar until there is no obvious liquid and there is no adhesion or agglomeration between the particles. Then put it in a vacuum drying oven, the pressure in the oven drops to 500 Pa, and start heating and drying. The drying temperature is 100°C and the drying time is 24 h.

[0156] (2) Place the treated sample in a vapor deposition furnace for coating. Pure acetylene is selected as the coating gas for carbon source deposition, and plasma is used for acetylene decomposition deposition. The deposition time is 48 hours. The plasma source is generated by an electron sputtering radio frequency gun with graphite as the target. The material table in the deposition chamber is set to a bias voltage of -400V to ensure the deposition of the carbon source. After the plasma is stable, the gas pressure in the chamber is controlled by a vacuum valve and maintained at 100Pa.

[0157] (3) The samples after vapor deposition are graded, and the materials are screened and adjusted to a target particle size; they are then placed in a vacuum drying oven and vacuum dried at 100° C. for 24 hours to form a finished negative electrode material.

[0158] Various performance tests were carried out on the negative electrode materials in the above-mentioned Examples 1-7 and Comparative Examples 1-2. The test results are shown in Table 1. Figure 1 , Figure 2 The isothermal adsorption-desorption curves of the negative electrode materials prepared in Example 1 and Comparative Example 1 are also given respectively.

[0159] Table 1 Test results of negative electrode materials of Examples 1-7 and Comparative Examples 1-2

[0160]

[0161] The electrochemical performance tests were also carried out on the negative electrode materials in the above-mentioned Examples 1-7 and Comparative Examples 1-2. The specific test results are shown in Table 2.

[0162] The battery sample production process is as follows: the specific capacity of the negative electrode material and the first charge and discharge coulomb efficiency are in accordance with the equipment and methods of BTRTC / ZY / 01-020 "Button Battery Method Operation Instructions": Assemble into button batteries. Among them, the counter electrode uses a metal lithium sheet, the separator is a PP-PE-PP composite film with a diameter of 19.2mm; the electrolyte component ratio is EC / EMC / DMC=1:1:1, and the lithium salt (LiPF6) concentration is 1.05mol / L.

[0163] Electrochemical performance test:

[0164] Material capacity test: Use button battery charging and discharging equipment, 0.1C constant current charging to 10mV, then 0.02C constant current charging to 5mV, and 0.1C constant current discharging to 1.5V cutoff.

[0165] Half-battery 50-week cycle test: using button cell charging and discharging equipment, in the first week, 0.1C discharge to 0.01V, 0.01C discharge to 0.01V, 0.01C discharge to 0.005V, 0.1C charge to 1.5V; in the second week, 0.2C discharge to 0.01V, 0.02C discharge to 0.01V, 0.02C discharge to 0.005V, 0.2C charge to 1.5V; in the third week, 0.5C discharge to 0.0 1V, 0.05C discharge in equal steps to 0.01V, 0.05C discharge to 0.005V, 0.5C charge to 1.5V; from the 4th to the 50th week, 1C discharge to 0.01V, 0.1C discharge in equal steps to 0.01V, 0.1C discharge to 0.005V, 1C charge to 1.5V; in the 51st week, 0.1C discharge to 0.01V, 0.01C discharge in equal steps to 0.01V, 0.01C discharge to 0.005V.

[0166] Full battery performance test: Graphite is mixed into the negative electrode material to make the capacity reach the standard 450mAh / g. The capacity retention rate of 0.2C charge and discharge is tested at high temperature (60°C) for 7 consecutive days (2.75V-4.2V).

[0167] Table 2 Electrochemical performance test results of negative electrode materials of Examples 1-7 and Comparative Examples 1-2

[0168]

[0169]

[0170] It should be noted that the adsorption equilibrium curve and the hysteresis loop area are numerical expressions of the surface pore structure distribution, which can affect the electrochemical properties of the material. Through the corresponding synthesis technology, the pore structure can be fine-tuned to improve the performance of the material, and different cores also have a certain impact on the material.

[0171] It can be seen from Table 2 that: Comparative Example 1 uses a single carbon source to coat the material, and the pore structure changes are relatively simple, and its hysteresis loop area is relatively small. Outside the optimization range, this situation will cause the pole piece to expand. This is because the pore structure is simple, which is conducive to electrolyte infiltration, but the surface side reaction is uncontrolled. In Example 7, by mixing auxiliary gas in the carbon source gas, the pore structure in the carbon layer during the carbon deposition process and the pore structure between the carbon layer and the carbon layer can be regulated, so that different pore structures and pore distributions can be formed inside the coating layer, and the hysteresis loop area is increased, which is conducive to alleviating the expansion of the core and stabilizing the SEI growth interface. Compared with Comparative Example 1, the expansion rate of the buckle electrode sheet of Example 6 has been significantly reduced, and the corresponding cycle capacity retention rate has also shown a huge difference. Combined with the test results of Comparative Example 1 and Example 7 in Table 1, this shows that the differentiated ratio ΔΦ of the pore structure can describe the electrochemical changes caused by the pore structure of the negative electrode material. When ΔΦ is within a suitable range, it can improve the electrolyte infiltration of complex pore structures and improve the transfer of active lithium in the electrolyte, thereby improving the rate performance. The complex pore structure provides a weak polarization transmission barrier for the thermal conduction of lithium ions, which is beneficial to limit the degradation reaction at high temperature and improve the high-temperature storage capacity retention rate.

[0172] In the preparation methods of negative electrode materials in Example 1 and Comparative Example 2, both use the same lithiated core, but different coating processes are used to regulate the pore structure of the surface coating layer, so that the differential ratio ΔΦ of the pore structure of the obtained negative electrode material is different. Although the hysteresis loop area ΔS of Comparative Example 2 is within the preferred range, the calculated differential ratio ΔΦ of the pore structure exceeds the preferred range and is 0.568. Combined with the electrochemical performance test results in Table 2, it can be seen that the pore structure in the coating layer of the negative electrode material prepared in Comparative Example 2 is very complex. During charging and discharging, there are a large number of electrolyte degradation byproducts (SEI) in the pores of the surface coating layer of the negative electrode material. Then, after the volume expansion of the lithiated silicon-based core, it will destroy the pore structure filled with electrolyte, and then tear the surface coating layer, causing the electrolyte degradation to be out of control. Although the expansion rate of the negative electrode sheet is improved, the rate performance is reduced. The rate charging performance of Comparative Example 2 in Table 2 at three rates of 1C / 0.5C, 2C / 0.5C, and 3C / 0.5C are respectively reduced by 3.49%, 5.67%, and 5.75% compared with the rate charging performance of Example 1.

[0173] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0174] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, any of the above-mentioned claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A negative electrode material, characterized in that: It comprises a silicon-based material core and a coating layer formed on at least a portion of the surface of the silicon-based material core, wherein the coating layer has a pore structure; The differential ratio of the pore structure Satisfaction: 1×10 -3 ≤ΔΦ≤0.5; Wherein, ΔS is the area of ​​the hysteresis loop in the isothermal adsorption-desorption curve of the negative electrode material; s is the specific surface area of ​​the negative electrode material; ΔP is the interval difference of the relative pressure P / P0 corresponding to the hysteresis loop, 0<ΔP≤1; Q max is the maximum isothermal adsorption capacity of the negative electrode material.

2. The negative electrode material according to claim 1, characterized in that At least one of the following conditions is met: a. The silicon-based material core includes at least one of elemental silicon, silicon oxide, silicon carbide, silicon nitride, silicon phosphide, silicon sulfide, and silicon alloy; b. The coating layer comprises at least one of a carbonaceous material and a ceramic material; c. The mass of the coating layer is 0.5%-10% of the total mass of the negative electrode material; d. The thickness of the coating layer is 20nm-700nm; e. The silicon-based material core also includes a carbon-based substance; f. The silicon-based material core further includes a doped metal; g. The differential ratio ΔΦ of the pore structure satisfies 5×10 -3 ≤ΔΦ≤0.5; h. The area of ​​the hysteresis loop ΔS satisfies 4.5×10 -4 ≤ΔS≤2.5×10 -2 ; i. The specific surface area s of the negative electrode material is 0.5m 2 / g-15m 2 / g; j. The maximum isothermal adsorption capacity Q of the negative electrode material max ≤1.35mmol / g; k. The BJH average pore size of the negative electrode material is 5nm-20nm, and the BJH pore volume satisfies 1.0×10 -4 cm 3 / g≤V BJH ≤0.1cm 3 / g; 1. The pH of the negative electrode material is 6.0-12.

0.

3. The negative electrode material according to claim 2, characterized in that At least one of the following conditions is also met: m. The carbonaceous material comprises at least one of graphite, hard carbon, soft carbon, amorphous carbon, diamond-like carbon, carbon fiber, carbide, asphalt, and resin-based polymers; n. The ceramic material includes at least one of phosphates, silicates, nitrides and metal oxides; o. The carbon material includes at least one of soft carbon, hard carbon, amorphous carbon, graphite, graphene, carbon nanotubes, carbon fiber, and diamond-like carbon; p. The doping metal includes at least one of Li, Mg, Al, Ti, Na, K, Ca, Be, La, Ce, V, and Ba; q. The mass percentage of the doped metal in the negative electrode material is 2%-15%.

4. The negative electrode material according to any one of claims 1 to 3, characterized in that The pore structure of the coating layer includes micropores, mesopores and macropores.

5. A method for preparing a negative electrode material, characterized in that: include: Performing CVD vapor deposition treatment on the silicon-based material core to be coated to obtain a negative electrode material with a pore structure in the coating layer; The gas for vapor deposition includes a mixed gas including an auxiliary gas and a carbon source gas.

6. The preparation method according to claim 5, characterized in that: At least one of the following conditions is met: A. Before the CVD vapor deposition process, the silicon-based material core to be coated is pretreated; B. The temperature of the vapor deposition treatment is 400°C-1200°C, and the time is 1h-12h; C. When the CVD vapor deposition process is performed, it also includes: placing the silicon-based material core to be coated in a deposition chamber of a deposition furnace, the rotation speed of the deposition chamber is 0.1r / min-10r / min, and the gas pressure in the deposition furnace is 0.1MPa-10MPa; D. The carbon source gas includes at least one of methane, ethane, ethylene, acetylene, propane, formaldehyde, acetaldehyde, and methanol; E. The auxiliary gas includes at least one of H2, SO2, NH3, and Ar; F. In the mixed gas, the volume proportion of the carbon source gas is 30%-95%, and the volume proportion of the auxiliary gas is 5%-70%.

7. The preparation method according to claim 6, characterized in that: At least one of the following conditions is also met: G. The pretreatment comprises: screening, grading, cleaning and drying the silicon-based material core to be coated in sequence; H. The particle size D of the silicon-based material core to be coated obtained after the pretreatment 50 =2.5μm-9.0μm; I. The specific surface area of ​​the silicon-based material core to be coated obtained after the pretreatment is 0.5 m 2 / g-7.5m 2 / g.

8. The preparation method according to claim 7, characterized in that: At least one of the following conditions is met: J. The cleaning comprises: first washing with water and then rinsing with an organic solvent; K. The drying comprises: air-drying the cleaned material using an inert gas, and then vacuum drying the cleaned material in an environment of 60° C.-150° C. and below 1000 Pa.

9. The preparation method according to any one of claims 5 to 8, characterized in that: After the vapor deposition process, the method further includes: classifying and drying the product obtained by the vapor deposition process.

10. A lithium ion battery, characterized in that: The negative electrode material comprises the negative electrode material according to any one of claims 1 to 4, or the negative electrode material prepared by the preparation method according to any one of claims 5 to 9.

Citation Information

Cited By

  • Negative electrode material and preparation method therefor, and lithium-ion battery

    EP4601035A1

  • Negative electrode material and secondary battery

    WO2026149360A1